ANALISIS KINERJA KEUANGAN PT.SEPATU BATA INDONESIA TBK SEBELUM DAN SAAT PANDEMI COVID-19 - Puspitasari, Hesti; Prihastiwi, Diah Agustina (Transpublika Publisher, 2022)
Assesing the Finansial Performance of PT. Sepatu Bata Indonesia Tbk before and during the Covid-19 Pandemic is a study conducted with the aim of looking at the company’s financial performance including the level og liquidity, solvency, and profitability. This research is a quantitative descriptive study using secondary data obtained from the PT. Sepatu Bata Indonesia Tbk's official website for the Indonesia Stock Exchange (IDX). The sample is the annual report of PT. Sepatu Bata Indoensia Tbk for the period of 2016-2020. The financial analysis used is a ratio analysis which includes liquidity ratios, solvency ratios, and profitability ratios. The findings revealed that the Covid-19 pandemic has an effect on the company's financial performance. Especially in the calculation of net profit margin (NPM, return on asset (ROA), and return on equity (ROE), this is because sales in 2020 experienced a significant decline. Thus, the net profit obtained in 2020 also decreased to minus Rp177.761.030.000, net profit recorded a new history for PT. Sepatu Bata Indonesia Tbk for the last five years. Research related to financial performance analysis is significant, especially with the expansion of research and the use of other financial analysis tool such as Common-Size by focusing on certain items in the balance sheet report.